2007
DOI: 10.1038/ni1502
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for a germline-encoded T cell receptor–major histocompatibility complex interaction 'codon'

Abstract: All complexes of T cell receptors (TCRs) bound to peptide-major histocompatibility complex (pMHC) molecules assume a stereotyped binding 'polarity', despite wide variations in TCR-pMHC docking angles. However, existing TCR-pMHC crystal structures have failed to show broadly conserved pairwise interaction motifs. Here we determined the crystal structures of two TCRs encoded by the variable beta-chain 8.2 (V(beta)8.2), each bound to the MHC class II molecule I-A(u), and did energetic mapping of V(alpha) and V(be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
259
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(286 citation statements)
references
References 46 publications
15
259
0
1
Order By: Relevance
“…This hypothesis is supported by a substantialnumberof crystal structures involving six different Vb8.2 TCRs and one Vb8.1 TCR in complex with mouse I-A molecules. These structures show close convergence of the CDR1b and CDR2b contacts with the I-A a1 chain helix (Reinherz et al 1999;Feng et al 2007;Dai et al 2008;Garcia et al 2009). This Vb8 interaction motif has been seen in structures with different I-A alleles, Va segments, and peptides, and mutation of these TCRb residues reduced or abolished activation by a panel of T cells.…”
Section: Structural Insights Into the Mechanism Of Mhc Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by a substantialnumberof crystal structures involving six different Vb8.2 TCRs and one Vb8.1 TCR in complex with mouse I-A molecules. These structures show close convergence of the CDR1b and CDR2b contacts with the I-A a1 chain helix (Reinherz et al 1999;Feng et al 2007;Dai et al 2008;Garcia et al 2009). This Vb8 interaction motif has been seen in structures with different I-A alleles, Va segments, and peptides, and mutation of these TCRb residues reduced or abolished activation by a panel of T cells.…”
Section: Structural Insights Into the Mechanism Of Mhc Restrictionmentioning
confidence: 99%
“…In a series of biochemical studies that included a broad representation of receptor complexes, a set of common features was identified Garrity et al 2005;Feng et al 2006;Feng et al 2007). First, in every case investigated, the association required both aspartic acid residues; alanine substitution of only one in the pair invariably resulted in dramatic assembly defects.…”
Section: Conservation Of Membrane-based Receptor Complex Assemblymentioning
confidence: 99%
“…One open and interesting controversy is whether it is a germ-line-encoded structure of all TCRs that predisposes the diagonal MHC binding or whether it is a result of positive and negative selection (14). Very recently, structural evidence has suggested that TCRs possess germ-line-encoded structures in their variable regions that recognize MHC molecules independent of the bound peptide (15). These germ-line-encoded TCR-MHC interactions would allow a fast screening of many different pMHCs presented on the target cell by a TCR (16) and might be reflected by the first fast association of the TCR CMV with MHC, as observed by Gakamsky et al Systematic mutations of the TCR and pMHC combined with structural and kinetic measurements could resolve this issue.…”
mentioning
confidence: 99%
“…Recent functional data revealed the important role of Y at position 48 of the hTRBV chain in T-cell positive selection, through contacts with the a domains of both class I and class II MHC molecules [17,34]. Strikingly, the BV5 genes (highly expressed both in humans and humanized mice) present this Y at position 48.…”
Section: Discussionmentioning
confidence: 99%